In situ electrochemical characterization of a microbial fuel cell biocathode running on wastewater - Ramanaiah, Sudarsu V. (2021)
The electrochemical features of microbial fuel cells’ biocathodes, running on wastewater, were evaluated by cyclic voltammetry. Ex situ and in situ electrochemical assays were performed and the redox processes associated with the presence of microorganisms and/or biofilms were attained. Different controls using sterile media (abiotic cathode microbial fuel cell) and membranes covering the electrodes were performed to evaluate the source of the electrochemistry response (surface biofilms vs. biotic electrolyte). The bacteria presence, in particular when biofilms are allowed to develop, was related with the enhanced active redox processes associated with an improved catalytic activity, namely for oxygen reduction, when compared with the results attained for an abiotic microbial fuel cell cathode. The microbial main composition was also attained and is in agreement with other reported studies. The current study aims contributing to the establishment of the advantages of using biocathodes rather than abiotic, whose conditions are frequently harder to control and to contribute to a better understanding of the bioelectrochemical processes occurring on the biotic chambers and the electrode surfaces.